LIS Research in the US and Canada: Are the Differences Cultural or Methodological? - Mittermeyer, Diane (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper pertains to an aspect of LIS research which is seldom addressed in the literature–that of replication. the first phase of The Canadian Public Library Effectiveness Study replicated the Preference component of Van House and Shilders' study entitled The Public Library Effectiveness Study. The purpose of the paper is two-fold. First it examines closely one of the explanations advanced by. . .